Child-parent agreement on Oral Health Knowledge, Self-Perception, and Behavior in Late Childhood and Early Adolescence - Silva, Mayron Guedes; Diniz, Ana Carolina Soares; Rodrigues , Vandilson Pinheiro; Claudia Costa Ribeiro, Cecilia; Firoozmand, Leily Macedo (Revista Sustinere, 2024)
This study aimed to investigate the proportion of agreement between parents and children on oral health knowledge, self-perception, and behavior in students aged 8–14 years. A cross-sectional study was conducted with 135 elementary school student-parent dyads. The participants completed a structured questionnaire that included closed questions with dichotomous and 5-point Likert scale items covering aspects related to their knowledge, beliefs, and myths about oral health, as well as their self-perception and behaviors. The proportion of child-parent agreement was calculated for each variable. Data were analyzed using Chi-square and Fisher’s exact test. Multivariate linear regression models were performed to evaluate predictors of agreement. Child-parent dyads had significant agreement levels in most responses regarding oral health knowledge/beliefs than oral health self-perception and behaviors. The proportion of agreement was higher in questions about the relationship between sugar and dental caries (0.95, 95% CI: 0.90–0.98), the preventability of dental caries (0.94, 95% CI: 0.89–97), and the protective effect of tooth brushing (0.94, 95% CI: 0.88–0.97). In the multivariate regression model, the child’s older age (Beta = 0.552, P = 0.003) and the higher parent education level (Beta = 0.254, P = 0.023) were predictors for greater agreement on oral health knowledge. The findings suggest that children and parents have high agreement on oral health knowledge; however, their agreement regarding oral health self-perception and behavior is low.